The Impact of CLIL on Students' English Skills and Competences in Primary School - Alfia Sari; Sri Rachmajanti; Mirjam Anugerahwati (JEELS (Journal of English Education and Linguistics Studies), 2024)
Studies investigating the implementation of content language integrated learning (CLIL) have been widely conducted in response to the use of English as a lingua franca. However, they are mostly conducted in secondary to higher education where students have acquired their L1. They are also limited to primary education and have largely examined the teachers’ perspectives. Therefore, this study investigated the impact of the CLIL implementation on students’ English proficiency and skills at primary school to look at the feasibility of this approach implemented in primary schools. Descriptive quantitative research is conducted to analyze and explain the English proficiency levels and skills of 64 third graders and 62 fourth graders in one primary school in Surabaya, Indonesia. The findings revealed that the CLIL approach implementation had positive impacts on students’ English acquisition. The students’ English proficiency levels were from basic to outstanding levels. They showed satisfied English average scores on writing, listening, and the use of English. They also demonstrated higher average scores on every skill component. This was due to the amount of English exposure and input the CLIL students received from the content-subject materials. The content material’s understanding, knowledge, and skill helped them acquire the target language. However, the students needed to improve their reading for detail skills as their scores were low.